Capturing the value of vaccination within health technology assessment and health economics: Country analysis and priority value concepts. Issue 30 (26th June 2022) - Postma, Maarten; Biundo, Eliana; Chicoye, Annie; Devlin, Nancy; Mark Doherty, T.; Garcia-Ruiz, Antonio J; Jaros, Patrycja; Sheikh, Shazia; Toumi, Mondher; Wasem, Jürgen; Beck, Ekkehard; Salisbury, David; et al.
Graphical abstract: Highlights: Economic evaluation (EE) considers few of 18 vaccination value concepts identified. Expert analysis identified 3 priority concepts to expand EE of vaccines. Selection criteria included decision-making relevance and measurement feasibility. Priorities: macroeconomic impact, social ethics/equity, health system strengthening. Relevant robust methods and evidence are needed to support new value elements in EE. Abstract: Background: A value of vaccination framework for economic evaluation (EE) identified unique value concepts for the broad benefits vaccination provides to individuals, society, healthcare systems and national economies. The objectives of this paper were to work with experts in developed countries to objectively identify three priority concepts to extend current EE. Methods: The previously developed classification of value concepts in vaccination distinguished 18 concepts, categorised as conventional payer and societal perspective concepts and novel broader societal concepts. Their inclusion in current EE guidelines was assessed. Experts identified eight criteria relevant to decision-making and measurement feasibility, which were weighted and used to score each concept. The relative ranking of concepts by importance and the gaps in guidelines were used to identify three priority concepts on which to focus immediate efforts to extend EE. Results: The EE guidelines review highlighted differences across countries and between guidelines and practice. Conventional payer perspective concepts (e.g., individual and societal health gains and medical costs) were generally included, while gaps were evident for conventional societal perspective concepts (e.g., family/caregiver health and economic gains). Few novel broader societal benefits were considered, and only in ad hoc cases. The top-three concepts for near-term consideration: macroeconomic gains (e.g., benefiting the economy, tourism), social equity and ethics (e.g., equal distribution of health outcomes, reduced health/financial equity gaps) and health systems strengthening, resilience and security (e.g., efficiency gains, reduced disruption, increased capacity). Conclusions: Gaps, inconsistencies and limited assessment of vaccination value in EE can lead to differences in policy and vaccination access. The three priority concepts identified provide a feasible approach for capturing VoV more broadly in the near-term. Robust methods for measuring and valuing these concepts in future assessments will help strengthen the evidence used to inform decisions, improving access to vaccines that are demonstrably good value for money from society's point of view.